Why the European Commission is Wrong to Push for a European Financial Transactions Tax - Lysandrou, Photis (Politik, 2013)
A financial activities tax (FAT) and a nancial transactions tax (FTT) represent alternative ways of taxing the nancial sector. In preparing a common proposal for the European Union, the European Commission initially appeared to favour the FAT but then swung its weight behind the FTT in late 2011. Its reasoning was that in addition to generating revenue this tax could also help to stabilize the nancial markets by curb- ing excessive speculative trading. is paper takes a di erent position. It argues that the FTT would amplify rather than dampen market instability by interfering with the functions of important nancial institutions. Its conclusion is that the FAT would be superior to the FTT.